Safety of wide-awake local anesthesia with no tourniquet (WALANT) in for lower limb surgery: A potential alternative in times of emergency - Bajuri, Mohd Yazid; Saidfudin, Nur Sai’dah; Mazli, Norliyana; Azriq, Nik Alif; Azemi, Aina Fatini (Frontiers in Surgery, 2022)
Lower limb surgery is usually performed under general or regional anaesthesia in normal operating room setting. However, when the surgery need to be performed in situations where there are limited resources and equipment, especially during a pandemic outbreak, in battlefields or area of disaster occurrence, the wide-awake local anaesthesia no tourniquet (WALANT) surgery can be utilised. This study aims to assess the efficacy of performing lower limb surgery using WALANT technique. A randomised cross-sectional study was designed to assess the effectiveness of WALANT in lower limb surgery, particularly in terms of duration of anaesthesia, Hamilton Anxiety Rating Scale (HAM-A), pain visual analogue scale (VAS), duration of surgery, amount of estimated blood loss (EBL) and total length of stay (LOS). A total of 91 patients requiring lower limb surgery were recruited, with only 83 patients completed the VAS pain assessment for all time points of the study. Mean age of patients was 52.1 ± 14.9 years. Mean VAS score were 1.19 ± 1.53 and 1.46 ± 1.86, preoperatively and intraoperatively. Mean VAS score were 0.55 ± 1.52, 0.60 ± 1.41, and 1.06 ± 1.69 at 2, 4, and 6 h post-surgery, respectively. Majority (79; 86.8%) of patient has preoperative anxiety score that was <17. Mean surgery duration was 65.28 ± 39.02 min, mean EBL was 91.34 ± 78.94 cc, whereas mean LOS was 3.35 ± 1.16 days. EBL was a weak predictor of postoperative pain. In conclusion, WALANT technique for lower limb surgery is effective and safe.